CT and MR arthrograms demonstrate a consistent communication between the tibiofemoral and superior tibiofibular joints. Issue 2 (10th May 2012) - Puffer, Ross C.; Spinner, Robert J.; Murthy, Naveen S.; Amrami, Kimberly K.
Abstract Communications between the tibiofemoral and superior tibiofibular joints (STFJ) have been thought to be infrequent. Previous anatomic studies have revealed these in only 10–64% of cases. In this study, the authors reviewed the results of direct knee arthrography performed in 17 consecutive patients from January 2010 to July 2011 with various knee or STFJ‐related pathologies. In all 17 consecutive cases, the authors demonstrated evidence of knee and STFJ communications. The authors believe that high‐resolution imaging arthrography, especially with physiological loading and delayed imaging, can demonstrate these communications more consistently than unenhanced anatomic studies. Clin. Anat. 2013. © 2012 Wiley Periodicals, Inc.